2021
DOI: 10.1002/mde.3529
|View full text |Cite
|
Sign up to set email alerts
|

The impact of political connection and board diversity on company performance: Evidence from China

Abstract: This paper examines the impact of political connection and board diversity on company performance. The sample is composed of information on Chinese‐listed companies from 2008 to 2016. We find a significantly negative correlation between political connection and company performance. Board diversity also has a significantly negative impact on company performance. However, when the impact of the interaction between political connection and board diversity is taken into consideration, we find that it can increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The control variables encompass firm age (in years), size (the natural logarithm of firm's total assets), firm location (1 for the capital city of Tallinn, 0 for other), mean of the biological age of individuals on the board (in years), women on the board (1 for at least one woman on the board), and mean of the time spent on the board (in years). These controls have been frequently used in the empirical studies on the relationship between political connectedness and firm performance, with recent examples of board member age in Liang et al (2022) and Xia et al (2019), board member gender and firm region in Wu et al (2018), board tenure in Kuzman et al (2018), and firm age and size in He et al (2019) and Liu et al (2021). We also included industry dummy variables to control for industry fixed effects (referred to as "Industry FE").…”
Section: Methodsmentioning
confidence: 99%
“…The control variables encompass firm age (in years), size (the natural logarithm of firm's total assets), firm location (1 for the capital city of Tallinn, 0 for other), mean of the biological age of individuals on the board (in years), women on the board (1 for at least one woman on the board), and mean of the time spent on the board (in years). These controls have been frequently used in the empirical studies on the relationship between political connectedness and firm performance, with recent examples of board member age in Liang et al (2022) and Xia et al (2019), board member gender and firm region in Wu et al (2018), board tenure in Kuzman et al (2018), and firm age and size in He et al (2019) and Liu et al (2021). We also included industry dummy variables to control for industry fixed effects (referred to as "Industry FE").…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Kim et al (2013) studied the effect of boards with diverse political ideologies on firm performance. They concluded that boards with political diversity are linked with higher firm performance (Liang et al, 2021). While the literature in this field is scarce, it might apply in Mauritius.…”
Section: Political Connections Board Ethnicity and Value Relevancementioning
confidence: 99%
“…(2013) studied the effect of boards with diverse political ideologies on firm performance. They concluded that boards with political diversity are linked with higher firm performance (Liang et al. , 2021).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Empirical evidence of board diversity generates various results. For example, heterogenous board has long-term impact on company goals (Naciti, 2019); diversity adversely influences company performance (Liang, Lin, Yu, and Li, 2021); and diversity is insignificant for large company to innovate (Zona et al, 2013). However, most results agree that diversity plays an important role in establishing board functions.…”
Section: Introductionmentioning
confidence: 99%